Leader's Entrepreneurial Resilience a Strong Predictor of New Hotel Performance in Yogyakarta - Denny Bernardus Kurnia Wahyudono (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
Yogyakarta as one of the leading tourism cities in Indonesia continues to show a trend of new hotel growth in recent years. Even though the Covid-19 pandemic has destroyed the hospitality sector globally, including in Indonesia, it turns out that new hotels are still popping up in this city. This is an interesting phenomenon indicating investor interest in continuing to invest in the hotel sector is still high. On the other hand, the presence of these new hotels keeps the hotel business competition competitive. In this situation, an innovative strategy becomes a determining factor for the sustainability of new hotels in the hotel business competition. The formulation of innovative strategies cannot be separated from the capabilities of the leaders of these new hotels. therefore, this study aims to observe the performance of 80 new hotels in Yogyakarta. The performance of the new hotel will be assessed from the perspective of leader capabilities which include entrepreneurial resilience and entrepreneurial self-efficacy. The findings of this study indicate that the leader's entrepreneurial resilience has a significant effect on the performance of the new hotels. Leader's entrepreneurial self-efficacy is also found to strengthen the effect of entrepreneurial resilience on new hotel performance.